Parry Romberg Syndrome: A Case Report - Coşkun, Başak Kandi; Saral, Yunus; Ataseven, Arzu; Öztürk, Perihan (Fırat University, 2004)
PRS is an atrophic dysplasia of the superficial facial tissues and it may destroy muscles, cartilage and bone. The etiology of PRS is unknown. PRS usually affects cheecks, forehead and lower jaw. In this article we presented a five years old case of PRS.

Parry Romberg sendromu (PRS) süperfisiyal fasial dokuyu, alttaki kas, kartilaj ve kemiği etkileyebilen atrofik bir displazidir. Etyolojisi belli değildir. Hastalık genellikle yanak, alın ve çene üzerinde gelişir.Bu makalede beş yaşında PRS'li bir olgu sunulmaktadır.
Parry Romberg Sendromu: Bir Olgu Sunumu